2001
DOI: 10.1677/joe.0.1680227
|View full text |Cite
|
Sign up to set email alerts
|

Administration of unmodified prolactin (U-PRL) and a molecular mimic of phosphorylated prolactin (PP-PRL) during rat pregnancy provides evidence that the U-PRL:PP-PRL ratio is crucial to the normal development of pup tissues

Abstract: During rat pregnancy initial high concentrations of prolactin (PRL) decline by about day 9, concomitant with an increase in the ratio of unmodified to phosphorylated PRL. The physiological significance of both the decline in total PRL and the change in ratio of the two PRLs is unknown. To test the importance of each, either unmodified PRL (U-PRL) or a molecular mimic of phosphorylated PRL (PP-PRL) were continuously administered to rats throughout pregnancy. A dose of 6 µg/24 h resulted in circulating concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
2

Year Published

2002
2002
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 43 publications
2
30
0
2
Order By: Relevance
“…No other normal tissues seem affected by treatment at this level (a dose that produces ∼50 ng/ml in the circulation) in adult animals, even if treatment is continued for one year. If S179D PRL is delivered to dams (at the same dose as for adult males) throughout pregnancy, the pups are born with increased apoptosis in the thymus and lungs (Yang et al,2001). This was an unexpected result since one would have expected the very much higher concentrations of placental lactogens to swamp out any effect of S179D PRL.…”
Section: S179d Prl Promotes Apoptosismentioning
confidence: 99%
See 1 more Smart Citation
“…No other normal tissues seem affected by treatment at this level (a dose that produces ∼50 ng/ml in the circulation) in adult animals, even if treatment is continued for one year. If S179D PRL is delivered to dams (at the same dose as for adult males) throughout pregnancy, the pups are born with increased apoptosis in the thymus and lungs (Yang et al,2001). This was an unexpected result since one would have expected the very much higher concentrations of placental lactogens to swamp out any effect of S179D PRL.…”
Section: S179d Prl Promotes Apoptosismentioning
confidence: 99%
“…This was an unexpected result since one would have expected the very much higher concentrations of placental lactogens to swamp out any effect of S179D PRL. Part of this effect may have been due to the anti-angiogenic effect of S179D PRL (see next section), but since S179D PRL was also found in the circulation of newborn pups (Yang et al, 2001), it also appears that PRL receptors (PRLR) exhibit some selectivity for ligand. S179D PRL is anti-angiogenic S179D PRL, but not unmodified PRL, has been shown to be anti-angiogenic in the chick chorioallantoic membrane and corneal angiogenesis assays (Ueda et al, 2006a).…”
Section: S179d Prl Promotes Apoptosismentioning
confidence: 99%
“…It was anticipated therefore that S179D PRL would impair the growth of tissues utilizing PRL as a growth factor by blocking the effects of both pituitary and autocrine PRL. Indeed, this molecule has been shown to impair the development of a number of fetal tissues (Coss et al 2000, Yang et al 2001, to inhibit the growth of mammary glands during pregnancy , Naylor et al 2005, to inhibit proliferation of human breast cancer cells in response to unmodified PRL (U-PRL) in vitro (Schroeder et al 2003) and to inhibit the growth of human prostate cancer cells both in vitro and when grown as tumors in nude mice .…”
Section: Introductionmentioning
confidence: 99%
“…Either U-PRL or S179D PRL was administered to adult male mice as a chronic infusion to produce levels around 150 ng/ml in the circulation (Yang et al, 2001), thereby mimicking the elevated levels associated with significant chronic stress (Almeida et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…However, studies in which the two major forms of PRL have been individually analyzed have shown them to have very different biological functions. Some of these studies used the naturally phosphorylated material (Krown et al, 1992, Wang and, while others utilized a stable molecular mimic of phosphorylated PRL, S179D PRL (Chen et al, 1998;Xu et al, 2001;Yang et al, 2001;Kuo et al,2002;Yang et al, 2002;Schroeder et al, 2003;Wu et al, 2003;Xu et al, 2003;Naylor et al, 2005;Guzman et al, 2005;Ueda et al, 2006a,b;Wu et al 2006). In the current study, we assessed the effects of either U-PRL or S179D PRL on LC and γδT in mature skin, in the absence or presence of a suberythemal dose of UVB.…”
Section: Resident Immune Cells Of the Skin Include Langerhans Cells (mentioning
confidence: 99%